2004
DOI: 10.1255/ejms.544
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption/Ionisation Time-of-Flight Mass Spectrometry. A Comparison of Fragmentation Patterns of Linear Dextran Obtained by In-Source Decay, Post-Source Decay and Collision-Induced Dissociation and the Stability of Linear and Cyclic Glucans Studied by In-Source Decay

Abstract: In the first part of this study fragmentation patterns from a range of dextran oligomers (containing 4-20 anhydroglucose units) were compared in three different methods of analysis coupled with matrix-assisted laser desorption/ionisation (MALDI) mass spectrometry. Collision-induced-dissociation (CID), prompt in-source decay (ISD) and post-source decay (PSD) all caused cleavage of the glycosidic bonds. Both CID and to a lesser extent ISD caused further cleavage of pyranose rings of the individual sugar residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…The results from LEISD of oligosaccharides obtained using laser of mJ level in this study were much distinct from those from traditional ISD reported [16][17][18][19][20][21]. Abundant fragmentation ions were obtained in this work, where laser power played an essential role.…”
Section: Influence Of the Laser Power On Isd Of Oligosaccharidescontrasting
confidence: 65%
See 2 more Smart Citations
“…The results from LEISD of oligosaccharides obtained using laser of mJ level in this study were much distinct from those from traditional ISD reported [16][17][18][19][20][21]. Abundant fragmentation ions were obtained in this work, where laser power played an essential role.…”
Section: Influence Of the Laser Power On Isd Of Oligosaccharidescontrasting
confidence: 65%
“…The fragmentations could be dynamically controlled; therefore, the intensities of ions could be described by Arrhenius equation, in which the front exponential factor A reflects the structural characteristics. There are some striking advantages of the LEISD method over the previously reported ISD methods [16][17][18][19][20][21], such as better S/N, more extensive fragmentation, and no interference from matrix ions. Better results obtained in positive-ion mode with continuous extraction in our experiments were probably because the laser energy (50 mJ per pulse) used here was much higher than that used in any previously reported ISD method.…”
Section: Linear Oligosaccharides With Different Linkagesmentioning
confidence: 98%
See 1 more Smart Citation
“…As glycans can be easily isolated and purified, the ISD and pMS 3 -sequencing approaches were also employed to characterize thoroughly the structures of both native [43,[54][55][56][57][58][59][60] and permethylated glycans [61][62][63][64][65][66], allowing unambiguous discrimination of isobaric species. In ref.…”
Section: Maldi-isd and Ptmsmentioning
confidence: 99%
“…M ALDI in-source decay (or MALDI ISD) has been observed for various kinds of analytes such as peptides and proteins [1][2][3][4][5][6], carbohydrates [7][8][9][10][11][12] oligonucleotides [13], and is currently used for top-down protein sequencing [14]. Concerning peptides and proteins, two main activation modes, thermal and radical-mediated, were described in literature to explain the in-source fragmentation pathways.…”
Section: Introductionmentioning
confidence: 99%